2022
DOI: 10.1155/2022/8432352
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the AC079305/DUSP1 Axis as Oxidative Stress-Related Signatures and Immune Infiltration Characteristics in Ischemic Stroke

Abstract: Background. Oxidative stress (OS) and immune inflammation play complex intersections in the pathophysiology of ischemic stroke (IS). However, a competing endogenous RNA- (ceRNA-) based mechanism linked to the intersections in IS has not been explored. We aimed to identify potential OS-related signatures and analyze immune infiltration characteristics in IS. Methods. Three datasets (GSE22255, GSE110993, and GSE140275) from the GEO database were extracted. Differentially expressed long noncoding RNAs, microRNAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The mRNA microarray technology based on gene expression profiles has facilitated the detection of a wide range of diseases [ 8 , 9 ]. The expression levels of several thousand genes have been measured simultaneously in these profiles for providing a better prognosis than prior models owing to the fact that they are used as the basis for the feature selection and classification [ 10 ]. The mechanism underlying the interactions between proteins and genes is being elucidated on a large scale using the high-throughput technologies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA microarray technology based on gene expression profiles has facilitated the detection of a wide range of diseases [ 8 , 9 ]. The expression levels of several thousand genes have been measured simultaneously in these profiles for providing a better prognosis than prior models owing to the fact that they are used as the basis for the feature selection and classification [ 10 ]. The mechanism underlying the interactions between proteins and genes is being elucidated on a large scale using the high-throughput technologies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a rat model of stroke, the depletion of T-lymphocytes led to smaller volumes of cerebral infarction and better recovery of neural function compared to controls ( 46 ); in patients with acute IS, T cells are activated in the peripheral blood ( 47 , 48 ). Monocytes in the blood may mediate neuroinflammatory responses and strongly influence IS outcomes ( 49 , 50 ). We found that lymphocyte levels were lower in patients with IS compared with healthy controls, while the levels of monocytes and neutrophils were higher.…”
Section: Discussionmentioning
confidence: 99%
“…The data were quantile normalized, and the differential expressed miRNAs (DEmiRNAs), mRNAs (DEmRNAs), and lncRNAs (DElncRNAs) between the IS and control samples were identified using R's limma package (v3.52.0) [19]. The P < 0.05, |log 2-fold change (FC)| > 0.5 were selected as cut-off criteria in identifying DEmRNAs and DEmiRNAs by previously reported methods [10,21,[28][29][30], and |log 2-fold change (FC)| > 1 was selected to identify DElncRNA [31,32]. Thereafter, volcano plots of DEmiRNAs, DElncRNAs, and DEmRNAs were generated using the ggplot2 package (v3.3.6) [33].…”
Section: Differential Expression Analysismentioning
confidence: 99%